Economic and social resilience: an analysis for the Italians regions after 2007. - Barbara Martini (European Regional Science Association (ERSA), 2014)
Resilience is a physical, engineering and ecological concept. Recently it has attracted attention from regional analyst and it could be a key aspect of the dynamic of spatial economic system (Reggiani et al., 2002), especially concerning how such system responds to shocks, disturbances, and perturbations. The concept of economic resilience is not unitary. We will use the adaptive resilience, defined as the ability of a system to undergo anticipatory or reactionary reorganization of form and/or function so as to minimize impact of a destabilizing shock. In this case the focus is on adaptive capability of system (Sammie e Martin, 2010). Following this approach resilience can be seen as a complex phenomenon and it can be divided in four interrelate dimensions (Martin, 2012): resistance, recovery re-orientation and renewal. We can also find some hysteresis a situation where one time disturbance permanently effect the path of the economy (Romer, 2001). The social resilience is the ability of individuals, organization and community to react, absorb or tolerate threat, stress, and risk (Adger, 2000) but it can be also defined as the ability of a social system to react, respond or recover after a disaster (Cutter, 2008). Several authors (Voss, 2008; Lorenz, 2010; Obrist et al., 2010; Benè et al., 2012) have underlined that three different types of capacities are necessary for understanding the notion of social resilience: coping capacities, adaptive capacities and transformative capacities. This dimension are closely related. The way they interact with each other depend on the context and on the capacity and ability of a given territory. Social capital (Bourdieu (1986) Coleman 1990 Putnam 1993, 1995, 2000) and social resilience are closely related. The aim of the paper is to examine whether and how Italian regions reacted in a resilient way after the economic shock in 2007 under the point of view of the social and economic dimension. As said resilience involves a complex circular feedback over these two dimensions. Our aim is to investigate in depth the nexus by means of suitable measures (indicators) built starting from elementary data collected by available data source (Bank of Italy survey on Household Condition and EU SILC data on living and social condition), exploiting the potential of multifactorial statistical analysis. Specially attention will be devoted to hysteresis.
Keywords: 330; social resilience; economic resilience; hysteresis; regional growth